Applicability of synthetic aperture radar in remote sensing flood area calculation - Yanyu Liu (Systems and Soft Computing)
Due to the influence of climate change, land use change, human activities, and other factors, flood disasters have shown a constantly increasing trend in the past few decades. Taking the flood disaster in Hebei Province, China in 2023 as an example, this study explores the applicability of synthetic aperture radar technology in remote sensing flood area calculation. Traditional flood area measurement methods have disadvantages such as high cost, difficulty in measurement, and limited accuracy. Based on this, this study uses SAR technology, with the help of GIS technology and case analysis methods, to process and analyze remote sensing flood area data. The study found that synthetic aperture radar technology has high applicability and accuracy in calculating the flood area of Hebei Province in 2023, and can effectively monitor and evaluate the impact of flood disasters on the region. Finally, this study also discusses the prospects for future development at both the technical and social levels, which will help improve flood monitoring and early warning capabilities, promote targeted poverty alleviation and post-disaster reconstruction work, and have important theoretical and practical significance for promoting the application of synthetic aperture radar technology in remote sensing flood area calculation.